Calengsai and the intimate communications among faith believers - Tjaturrini, Dyah; Arieshanty, Chendy; Asiati, Tri; Prasetyowati, Henggar; Isro, Zuyinatul (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2022)
Calung, Lengger, and Barongsai, abbreviated Calengsai, is a new-arising art appearing because of acculturation between communities, namely the Banyumas and Chinese people through adaptation. This adaptation is underpinned upon the teachings of each religion which teaches that every human being must be good to others. The aims of this study is to find the right solution to avoid the conflict and to analyse how culture can become the bonding element between religious communities This research was conducted in different cultural backgrounds and society that may elicit conflicts. There are several problems discussed in this research. First, how conflicts are resolved and how inter-religious relations are strengthened. Second, what the media is used to attach religious communities. To portray such issues, the writers conducted literary study, observation, and interviews. to analyse the data, the writers implemented the theory of cultural adaptation and cross-cultural communication. The result of this research is to provide an understanding that culture can strengthen the relationship between religious communities. To sum up, Calengsai has sociocultural values that arise as a result of cultural shifts in each society that can be used as an adhesive medium for inter-religious relations.